Pulse Wave Velocity is affected by the magnitude of the Pulse Wave, in human veins - Ermini, Leonardo; Roatta, Silvestro (Biomedical signal processing and control, 2023)
•Whether the magnitude of the Pulse Wave (PWm) affects the PWV was never previously experimentally investigated.•The Venous PWV measurement set-up allows to control the magnitude of the generated pulse wave.•In veins, a variation in the PWm linearly affects the corresponding PWV measurement.•PWm can be a confounding factor, also in arterial PWV measurements. Pulse Wave Velocity (PWV) is theoretically affected by the magnitude of the PW (PWm), in veins as well as in arteries, but, to our knowledge, this possibility has never been tested experimentally. Aim of this work is to investigate the dependence of PWV on PWm. The issue is investigated in limb veins, whereby PWs of different magnitude can be generated by controlled pneumatic compressions of the limb extremity. Venous PWV (vPWV) was measured using Doppler-US on the upper limb of 13 healthy volunteers in supine position, after 15 min of rest, using three different compression levels (100, 200, 300 mmHg of 1-s duration) in a randomized order. Eight compressions were delivered 15-s apart for each of the three levels. The peak frequency of the Doppler shift was used as an indication of PWm. The compression level had a statistically significant effect on both vPWV and PWm (p < 0.001), but the effect was reduced for those subjects exhibiting, at the lowest compression intensity, an already elevated vPWV value (exponential fitting, R2 = 0.66). The magnitude of the exogenously generated venous PWs significantly affected vPWV, suggesting that the delivery of the compressive stimulus should be carefully implemented and monitored. Further studies are needed to investigate the implications in arterial PWV assessment.